Erectile dysfunction in patients with substance abuse : a preliminary report in Bandung, West Java, Indonesia - Lucky S,; Kevin SW,; R, Angke; Luke WSC,; Hatta Sidi, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Substance abuse (psychoactive) has multiple adverse effects, i.e., biological, psychological, economic, social or legal. Among the biological effects, little is known about its impact on sexual function, especially erectile dysfunction (ED) in men. The study’s objective was to determine the patient’s risk factors of ED comorbid with substance abuse at the Methadone Maintenance Therapy Program Clinic (MMTPC), Hospital Dr. Hasan Sadikin Clinic, Bandung, Indonesia. This was a crosssectional study among patients at the MMTPC, Hospital Dr. Hasan Sadikin Clinic, Bandung, Indonesia. We obtained the ED data using the self-reporting International Index of Erectile Function (IIEF-5) questionnaire. Based on 30 respondents who attended the clinic, the age of the subjects ranged from 24-52 years, with a mean age of 40 years. The respondents with substance abused included those misusing opioids (N= 27, 90%), cannabis (N = 18, 60%), amphetamines (methamphetamines and ecstasy) (N= 10, 33.3%), benzodiazepine drugs (N= 7, 23.3%), alcohol (N= 2, 6.7%) and others (antidepressants and suboxone) (N= 2, 6.7%). ED occured in 90% of the respondents (n=27) where 64% (n=19) had mild, 23% (n=7) mild-moderate, 3% (N=1) moderate ED, and 10% (n=3) without an ED. There was no severe ED in the subjects of this study. Respondents without multiple drug abuse had a lower degree of ED with a median IIEF-5 score of 17.0 (IQR: 15.0-20.0) compared to those taking multiple substances (Median score = 20.0, IQR: 18.5-21.0). Respondents who reported cannabis use had a lower median IIEF-5 score of 17.0 (IQR: 15.0- 20.3), i.e., lesser ED than those with multiple drug substances (Median score = 19.5, IQR: 19.0-21.0). We performed additional analyses to identify variables, i.e., age, total type of drugs used, and duration of use in years associated with lower IIEF-5 scores and none of thosee variables showed a significant correlation with the IIEF-5 score (Spearman’s correlation coefficients >0.05). In conclusion, a high incidence of ED in substance abuse patients undergoing methadone maintenance therapy programmes requires special attention from healthcare workers during the consultation in MMTPC.